Approach to manage parameter and choice uncertainty in life cycle optimisation of building design: Case study of optimal insulation thickness. (15th March 2021) - Ylmén, Peter; Mjörnell, Kristina; Berlin, Johanna; Arfvidsson, Jesper
Abstract: In order to mitigate global warming, it is important to decrease the climate impact from the building stock, which accounts for 39% of the GHG emissions in Europe. An extensive portion of these emissions are generated from the heating of buildings, but emissions also occur from the production of building materials. It is therefore important to find building design solutions that consider both production and operation and maintenance in order to minimise the climate impact of a building during its entire lifetime. At the same time, the production of buildings has to be cost-efficient. In the design of buildings, both climate impact and cost must be evaluated in order to make well-supported decisions. The overall aim of this study was to develop a procedure to facilitate using life cycle studies as decision support for building design. The presented approach will provide a structured means to manage choice and parameter uncertainty when life cycle studies are used as decision support in order to optimise building design. There are many uncertainties in the design phase of buildings, and the approach is demonstrated here in a case study of insulation thickness in the building envelope. The results can be used to support decisions on where to effectively make improvements when subjective choices and parameter uncertainties are considered in the study. The suggested approach will lessen the problem of false certainty in the conclusions drawn, and at the same time provide strong decision support. Highlights: The study shows how to incorporate ECE and DCP in simulation of building design. The approach manages secondary effects and uncertainties in life cycle tools. Mitigate the risk for faulty conclusions regarding optimal building design.